Catheter Induced Urethral Injury in Surgical ICU of Tertiary Care Hospital in Nepal - Thapa, Niraj; Acharya, Ganesh Bhakta; Yogi, Nikunja; Ghimire, Pradeep; Sharma, Abhinav (Nepal Journal of Medical Sciences, 2024)
Introduction: Urethral catheterization is one of the most common procedures in urology. Most common complications of urethral catheterization is urethral injury. We conducted this study to find the prevalence of catheter induced urethral injury in surgical intensive care unit of tertiary care hospital in Nepal. Methods: A retrospective chart review was carried out in all patients admitted in surgical ICU in between January 2022 to January 2024. All cases who had iatrogenic urethral injury while catheterization was recorded with an aim of studying the prevalance, cause, implication and management of urethral injury in tertiary care hospital. Data collection was started after getting ethical approval from Institutional Review Committee of Manipal College of Medical Sciences (Reference number -MEMG/479/IRC). SPSS version 21.0 was used for data analysis, p-value less than 0.05 as statistically significant at 95% confidence interval. Results: Total 509 patients were taken for study. Thirty-six patients (7.07%) developed catheterization induced trauma. There were no significant differences when the catheterization was done by junior (6.56%) or senior health workers (8.59%) (p=0.44). Similarly, there was no statistically significant difference in injuries when catheterization was done during regular (5.36%) or on call hours (8.22%) (p=0.22). However, the mean number of attempts in catheterization before seeking help from the seniors had significant difference in the number of injuries (P<0.001) Conclusions: Prevalence of catheterization induced urethral injury was higher compared to past studies. Iatrogenic catheterization injuries represent a significant cause of patient morbidity. Most occur due to inadequate knowledge of catheterizations. Most injuries are seen to occur while multiple unsuccessful catheterization attempts.